ANALISIS YURIDIS TINDAKAN DIREKTUR UTAMA DANA PENSIUN BUKIT ASAM BERDASARKAN PRINSIP FIDUCIARY DUTY: Legal Analysis of Fiduciary Duty in The Action of The Bukit Asam Pension Fund President Director - Raja Abdurrafi Arifin Siregar; Arif Wicaksana (Faculty of Law, Universitas Trisakti, 2026)
The increase in life expectancy accompanied by a growing elderly population in Indonesia requires professional, responsible, and secure management of pension funds to ensure the welfare of participants in their retirement. Pension funds, as legal entities, are managed by a Board of Directors bound by the principle of fiduciary duty as a relationship of trust in the management and investment of participants' funds. However, errors in investment policy have the potential to cause losses and raise issues of legal liability for the Board of Directors. The problem formulation in this study is the liability of the Board of Directors for errors in investment placement in the Bukit Asam Pension Fund for the period 2013–2018 based on the principle of fiduciary duty and the application of the principle of piercing the corporate veil. The method used in this study is normative legal research with a descriptive qualitative approach, through a literature study of relevant laws, court decisions, and legal literature. The results and conclusion shows that these actions constitute a violation of fiduciary duty and cannot be classified as business risks protected by law. Therefore, the Board of Directors' liability is personal through the application of the piercing the corporate veil principle, so that limited liability protection can be set aside.